Solder alloy, solder paste, solder ball, solder preform, solder joint, onboard electronic circuit, ECU electronic circuit, onboard electronic circuit device, and ECU electronic circuit device
By adding elements such as Sb, Bi and As to the Sn-based welding material, a stable SnSb phase and As-enriched layer are formed, the weather resistance and reliability of welding materials under extreme temperatures and external forces are solved, and the efficiency and reliability of welding materials are achieved in automotive electronic circuit applications.
Patent Information
- Application Number
- JP2025003029
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-05-27
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-10
AI Technical Summary
The prior art is difficult to ensure the weather resistance and reliability of welding materials under extreme temperature environments and external forces. Especially in the application of automotive electronic circuits, there are problems of stress concentration of welding interfaces and interface failure under temperature cycling.
By adding elements such as Sb and Bi to the Sn-based welding material, the SnSb phase in solid-soluble and particulate states is formed. The effects of solid-solution strengthening and precipitation dispersion strengthening are used to improve the temperature cycling performance and resistance to external force of the welding material. At the same time, As is added to the welding material to form an As-enriched layer to inhibit the increase in viscosity of the welding paste.
The weather resistance of welding materials for long-term use in extreme temperature environments from -40°C to 125°C is achieved, and the stability and reliability of the welding interface are maintained under the action of external forces, while inhibiting the increase in viscosity of the welding paste.
Smart Images

Figure 2025061123000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a solder alloy, a solder paste, a solder ball, a solder preform, a solder joint, an on-vehicle electronic circuit, an ECU electronic circuit, an on-vehicle electronic circuit device, and an ECU electronic circuit device. [Background technology]
[0002] Automobiles are equipped with electronic circuits (hereafter referred to as on-board electronic circuits) that have electronic components soldered to a printed circuit board. On-board electronic circuits are used in devices that electrically control the engine, power steering, brakes, etc., and are extremely important safety components for the operation of an automobile. In particular, on-board electronic circuits called ECUs (Engine Control Units), which are electronic circuits that control the vehicle via computer to improve fuel efficiency, must be able to operate stably without failure for long periods of time. These ECUs are generally installed near the engine, which means that they are used in fairly harsh environments.
[0003] The area near the engine where such on-board electronic circuits are installed becomes extremely hot, at over 125°C, when the engine is running. On the other hand, when the engine is stopped, the outside air temperature drops to low temperatures, for example, below -40°C in winter in cold regions such as North America or Siberia. Therefore, the on-board electronic circuits are exposed to a heat cycle of below -40°C to above +125°C as the engine is repeatedly started and stopped.
[0004] When an in-vehicle electronic circuit is placed in such an environment where the temperature changes greatly for a long period of time, the electronic components and the printed circuit board each undergo thermal expansion and contraction. However, the difference between the linear thermal expansion coefficient of the electronic components and the linear thermal expansion coefficient of the printed circuit board is large, and a certain thermal displacement occurs in the soldered joints (hereinafter referred to as "solder joints") that join the electronic components and the printed circuit board during use in the above environment, so that repeated stress is applied due to temperature changes. This puts stress on the solder joints, and ultimately the joint interface of the solder joints breaks. In electronic circuits, even if the solder joints do not break completely, cracks may occur in the solder joints with a crack rate of 99% or less, and the resistance value of the circuit may increase and cause malfunction even if there is electrical conduction. If cracks occur in the solder joints and the in-vehicle electronic circuit, especially the ECU, malfunctions, it may lead to a serious automobile accident that is at the risk of human life. Thus, the temperature cycle characteristics are particularly important for in-vehicle electronic circuits, especially the ECU, and the most severe temperature conditions imaginable are required.
[0005] As an example of a solder alloy that can withstand such severe temperature conditions, Patent Document 1 discloses a lead-free solder for automotive use that is characterized by containing 2.8 to 4 mass% Ag, 1.5 to 6 mass% Bi, 0.8 to 1.2 mass% Cu, a total of 0.005 to 0.05 mass% of at least one type selected from the group consisting of Ni, Fe, and Co, and the balance being Sn.
[0006] Patent Document 2 also discloses a solder alloy having an operating temperature of 150° C. or higher, which comprises an alloy containing, in addition to Sn as the main component, 10 wt % or less of Ag, 10 wt % or less of Bi, 10 wt % or less of Sb, and 3 wt % or less of Cu, and which further contains 1.0 wt % or less of Ni. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] WO2009 / 011341A [Patent Document 2] JP 2006-524572 A Summary of the Invention [Problem to be solved by the invention]
[0008] As seen in the spread of hybrid and electric vehicles, the shift from mechanical to electronic components in automobiles is progressing, and accordingly, there is a demand for miniaturization of automotive electronic circuits, which previously had a margin of size. Conventionally, automotive electronic circuits were soldered by reflow soldering followed by flow soldering, but in recent years, double-sided reflow boards are being used in which both sides are surface-mounted with solder paste. Due to the high density of such automotive electronic circuits, a new crack mode has appeared in harsh environments, in which cracks propagate within Sn phase grains, in addition to the conventional cracks at Sn grain boundaries and between different phases.
[0009] Incidentally, Patent Document 1 discloses a solder alloy that has a long life in harsh environments, but since automobiles are used as a means of transportation, they are rarely left stationary in one place and are often used on roads, etc. When used on such roads, the on-board electronic circuit device is constantly subjected to vibration due to the rough road, and is often subjected to external forces such as running over a curb or colliding with the car in front. If the collision is a major accident, the entire on-board electronic circuit device is often replaced, but in the case of a simple contact accident, it is often enough to replace only the exterior of the car, and the on-board electronic circuit device must not only withstand harsh environments but also withstand external forces.
[0010] In addition, the solder alloy described in Patent Document 2 excludes Co from the solder alloy described in Patent Document 1 and contains Sb, but the range of the content of each constituent element is much wider than the range of the content of the solder alloy described in Patent Document 1. The solder alloy described in Patent Document 2 is intended to be usable at high temperatures, and the constituent elements are different from those of the solder alloy described in Patent Document 1. For this reason, it is doubtful whether the solder alloy described in Patent Document 2 can withstand harsh environments in the same way as the solder alloy described in Patent Document 1 in the entire content range described in Patent Document 2. In order to show good temperature cycle characteristics, the alloy composition needs to be reconsidered.
[0011] Furthermore, in the joining and assembly of electronic components to a substrate, soldering using a solder paste is advantageous in terms of cost and reliability. The application of the solder paste to a substrate is performed, for example, by screen printing using a metal mask. In order to ensure the printability of the solder paste, the viscosity of the solder paste must be moderate. Here, if the content of the activator is increased or a highly active one is used to improve the wettability of the solder paste, the viscosity of the solder paste increases over time. For this reason, conventional solder alloys cannot simultaneously satisfy the heat cycle characteristics and the viscosity increase suppression effect when used in a solder paste, and further consideration is required.
[0012] The problem that the present invention aims to solve is to provide a solder alloy that can withstand for a long period of time not only severe temperature cycle characteristics such as a low temperature of -40°C and a high temperature of 125°C, but also withstand for a long period of time external forces generated by running over a curb or colliding with a vehicle in front, and furthermore, can suppress changes in the viscosity of the solder paste over time. In addition to the above, the problem that the present invention aims to solve is to provide a solder paste, solder ball, and solder preform using the above solder alloy, a solder joint formed therefrom, and an on-vehicle electronic circuit, an ECU electronic circuit, an on-vehicle electronic circuit device, and an ECU electronic circuit device that include this solder joint. [Means for solving the problem]
[0013] The inventors have discovered that in order to withstand external forces after long-term temperature cycles, it is effective to create a solid-solution strengthened alloy by adding an element that dissolves in the Sn phase, that Sb is the optimal element for creating a solid-solution precipitation strengthened alloy, and that the addition of Sb to a Sn matrix forms fine SnSb intermetallic compounds, which also exhibit the effect of precipitation dispersion strengthening.
[0014] The metallurgical structure of the solder alloy according to the present invention is characterized in that the solder alloy has a structure in which Sb is dissolved in a Sn matrix, and the structure exhibits a stable Sb-dissolved state at high temperatures, for example, 125°C, but as the temperature decreases, Sb gradually dissolves in the Sn matrix in a supersaturated state, and at low temperatures, for example, -40°C, Sb precipitates as a SnSb intermetallic compound.
[0015] The reason why the solder alloy according to the present invention forms fine Sb precipitates even after being exposed to temperature cycles and does not suffer from structural deterioration such as coarsening of compounds is believed to be as follows.
[0016] Solder alloys to be joined by reflow soldering are subjected to a temperature cycle test of -40°C to +125°C, simulating a low temperature in a cold region and a high temperature in an engine room. In the solder alloy according to the present invention, the Sb contained therein is redissolved in the Sn matrix at a high temperature of, for example, 125°C, and a process in which an SnSb intermetallic compound is precipitated at a low temperature of, for example, -40°C is repeated. As a result, the coarsening of the SnSb intermetallic compound stops, and during the temperature cycle test, the SnSb metallic compound that was once coarsened is also redissolved in the Sn matrix at the high temperature side, so that fine SnSb intermetallic compound is formed, and the precipitation dispersion strengthened solder alloy is maintained.
[0017] However, when the Sb content exceeds 5.3 mass%, for example 8 mass%, the grain size of the SnSb compound does not become fine at the beginning of the temperature cycle test, and the liquidus temperature rises, so that the Sb does not re-melt even at the high temperature side and the original SnSb crystal grains are maintained. Therefore, even if the material is repeatedly used under the above-mentioned temperature cycle, fine SnSb intermetallic compounds are not formed.
[0018] Furthermore, if the Sb content exceeds 5.3 mass%, the liquidus temperature of the solder alloy rises, and soldering is not possible unless the reflow heating temperature is increased. In this way, if the reflow conditions are increased, Cu on the surface of the printed circuit board melts into the solder, and a thick layer of SnCu intermetallic compounds such as Cu6Sn5 is likely to form in the soldered portion with the printed circuit board, making the printed circuit board and the solder joint more likely to be destroyed.
[0019] In the present invention, a predetermined amount of Sb becomes fine precipitates in the form of a compound called SnSb in the Sn matrix of the solder alloy. The solder alloy according to the present invention can maintain the state of fine precipitates of SnSb intermetallic compounds in the Sn matrix even after nearly 3000 temperature cycles of -40 to +125°C. As a result, the SnSb precipitates inhibit cracks that tend to occur at the interface between electronic components and solder joints.
[0020] In addition, when the Bi content is 1.5 to 7 mass%, Bi substitutes for Sb, and the above-mentioned effects of Sb can be exhibited synergistically, but considering the above-mentioned alloy structure, it is considered that the two are closely related. A detailed investigation of the contents of both elements revealed that there is an appropriate range of Bi content depending on the Sb content.
[0021] In addition, the present inventors have attempted to add a small amount of As from among various elements to the Sn-Ag-Cu-Bi-Sb-Ni solder alloy, which has excellent temperature cycle properties as described above. It is known that a solder alloy with a high Sn content forms an SnO2 film as described above, and solder alloys containing As are generally considered to have poor wettability, so adding As to the solder alloy has been avoided. However, unexpectedly, the Sn-Ag-Cu-Bi-Sb-Ni-As solder alloy containing a predetermined amount of As maintains excellent wettability, and in addition to the above findings, the present invention has been completed based on the findings that an As-enriched layer is formed on the surface of the solder alloy, resulting in an excellent thickening suppression effect.
[0022] As described above, the excellent temperature cycle characteristics and the effect of suppressing thickening are not exhibited simultaneously when the content of even one of the constituent elements does not satisfy the range of the present invention, and these effects are exhibited simultaneously only when each element simultaneously satisfies the range of the present invention, as in the present invention. This is a finding that was first obtained with the solder alloy of the present invention.
[0023] The present invention, which was obtained based on these findings, is as follows. (1) A solder alloy comprising, by mass%, 1-4% Ag, 0.5-1.0% Cu, 1.5-5.5% Bi, and 1.0-5.3% Sb, or more than 5.5% Bi and up to 7.0% Sb, 2.0-5.3% Sb, 0.01-0.2% Ni, 0.0040-0.0250% As, and the remainder being Sn, the solder alloy having an As-enriched layer, the presence of which is confirmed by the following criteria, the As-enriched layer being a region from the outermost surface of the solder alloy to a depth of 2×D1 (nm) in terms of SiO2, and the As-enriched layer having a thickness in terms of SiO2 of 0.5-8.0 nm. (Judgment criteria) An arbitrary area of 700μm×300μm is selected from a sample measuring 5.0mm×5.0mm, and XPS analysis is performed in combination with ion sputtering. One area is selected for each sample, and three analyses are performed once for each of the three samples, for a total of three analyses. If S1>S2 in all three analyses, it is determined that an As-enriched layer has formed. Where: S1: In the XPS analysis chart, the integral value of the As detection intensity in the region of 0 to 2×D1 (nm) converted into SiO2 depth S2: The integral value of the As detection intensity in the region of SiO2 equivalent depth 2×D1 to 4×D1 (nm) in the XPS analysis chart D1: In the XPS analysis chart, the first SiO2 equivalent depth (nm) at which the detection intensity of O atoms becomes half the maximum detection intensity (intensity at Do·max) in a portion deeper than the SiO2 equivalent depth (Do·max (nm)) at which the detection intensity of O atoms becomes maximum.
[0024] (2) The lead-free solder alloy according to (1) above, further comprising, by mass%, 0.2% or less of In.
[0025] (3) The solder alloy according to (1) or (2) above, further comprising, by mass%, Co: 0.1% or less.
[0026] (4) A solder paste comprising a solder powder made of the solder alloy according to any one of (1) to (3) above and a flux.
[0027] (5) A solder ball made of the solder alloy according to any one of (1) to (3) above.
[0028] (6) A solder preform made of the solder alloy according to any one of (1) to (3) above.
[0029] (7) A solder joint formed from the solder alloy according to any one of (1) to (3) above.
[0030] (8) An on-vehicle electronic circuit comprising the solder alloy according to any one of (1) to (3) above.
[0031] (9) An ECU electronic circuit comprising the solder alloy according to any one of (1) to (3) above.
[0032] (10) An on-vehicle electronic circuit device comprising the on-vehicle electronic circuit according to (8) above.
[0033] (11) An ECU electronic circuit device comprising the ECU electronic circuit described in (9) above.
[0034] In the present invention, "on-board" means to be mounted on an automobile, and specifically means that the specified characteristics can be maintained and the product can be mounted on an automobile even when it is repeatedly exposed to a harsh usage environment, i.e., a temperature environment of -40° C. to 125° C. More specifically, the product can withstand a heat cycle test of 3000 cycles even in such a temperature environment, and has resistance to a shear test that evaluates an external force even under those conditions. [Brief description of the drawings]
[0035] [Figure 1] FIG. 1 is a schematic diagram showing a method for calculating the crack rate. [Diagram 2] Figure 2 is a chart of the XPS analysis of the solder ball surface. [Diagram 3] FIG. 3 is a chart of the XPS analysis of the solder ball surface. [Figure 4] FIG. 4 is a chart of the XPS analysis of the solder ball surface. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0036] The present invention will be described in more detail below. In the following description, "%" regarding the solder alloy composition is "mass %" unless otherwise specified.
[0037] 1. Solder alloy (1) Ag: 1-4% Ag has the effect of improving the wettability of the solder alloy and precipitates a network-like compound of intermetallic compound Ag3Sn in the solder matrix, creating a precipitation-dispersion strengthened alloy, thereby improving temperature cycle characteristics.
[0038] In the solder alloy according to the present invention, if the Ag content is less than 1%, the wettability of the solder alloy cannot be improved, and the amount of Ag3Sn precipitated is small, so that the network of the intermetallic compound is not strong. The lower limit of the Ag content is 1% or more, preferably 2% or more, and more preferably 3.3% or more. If the Ag content is more than 4%, the liquidus temperature of the solder alloy increases, and the remelting of the Sb added in the present invention does not occur, hindering the effect of refining SnSb. The upper limit of the Ag content is 4% or less, and preferably 3.5% or less.
[0039] (2) Cu: 0.5-1.0% Cu prevents Cu erosion of the Cu land, and also improves the temperature cycle characteristics by precipitating fine Cu6Sn5 compounds in the matrix of the solder alloy.
[0040] If the Cu content is less than 0.5%, the Cu erosion prevention effect on the Cu land is not observed. The lower limit of the Cu content is 0.5% or more, and preferably 0.65% or more. On the other hand, if the Cu content exceeds 1.0%, a large amount of Cu6Sn5 intermetallic compound is precipitated at the bonding interface, and the cracks grow quickly due to vibration, etc. The upper limit of the Cu content is 1% or less, and preferably 0.75% or less.
[0041] (3) Bi: 1.5-5.5% and Sb: 1.0-5.3% or Bi: more than 5.5% but not more than 7.0% and Sb: 2-5.3% In a temperature cycle test, Sb is dissolved in Sn at 125° C., and as the temperature decreases, Sb in the Sn matrix gradually becomes dissolved in a supersaturated state, forming a structure in which it precipitates as an SnSb intermetallic compound at −40° C. This allows the solder alloy of the present invention to exhibit excellent temperature cycle characteristics.
[0042] If the Sb content is less than 1.0%, the Sb content is too low and the effect of solid solution strengthening is not achieved. If the Sb content exceeds 5.3%, the liquidus temperature rises, and Sb does not remelt at high temperatures exceeding 125°C, which occurs when an engine is running under the hot sun, and the SnSb compound becomes coarse, making it impossible to prevent cracks from propagating within the Sn phase grains. Therefore, the Sb content of the solder alloy according to the present invention must be at least in the range of 1.0 to 5.3%.
[0043] Bi can further improve the temperature cycle characteristics. Sb not only precipitates SnSb intermetallic compounds to create a precipitation dispersion strengthened alloy, but also has the effect of distorting the Sn crystal lattice by penetrating into the Sn crystal lattice and replacing Sn, thereby improving the temperature cycle characteristics. At this time, if the solder alloy contains Bi, Bi, which has a larger atomic weight than Sb and has a greater effect of distorting the crystal lattice, replaces Sb, thereby further improving the temperature cycle characteristics. In addition, Bi does not prevent the formation of fine SnSb compounds, and the precipitation dispersion strengthened solder alloy is maintained.
[0044] If the Bi content is less than 1.5%, substitution with Sb is unlikely to occur and the effect of improving temperature cycles is not achieved. On the other hand, if the Bi content exceeds 7.0%, the ductility of the solder alloy itself decreases, making it hard and brittle, and cracks will grow quickly due to vibration, etc.
[0045] As described above, Sb and Bi can synergistically improve temperature cycle characteristics, etc., so the range of the Sb content is determined according to the range of the Bi content, and the contents of both elements in the solder alloy according to the present invention have a predetermined relationship. When the Bi content is 1.5 to 5.5%, the Sb content is 1.0 to 5.3%, and when the Bi content is more than 5.5% and not more than 7.0%, the Sb content is 2.0 to 5.3%.
[0046] When the Bi content is 1.5-5.5%, the lower limit of the Bi content is preferably 2.0% or more, and more preferably 3.0% or more. When the Bi content is 1.5-5.5%, the upper limit of the Bi content is preferably 5.2% or less. When the Sb content is 1.0-5.3%, the lower limit of the Sb content is preferably 2.0% or more, and more preferably 2.8% or more. When the Sb content is 1.0-5.3%, the upper limit of the Sb content is preferably 5.2% or less.
[0047] When the Bi content is more than 5.5% and not more than 7.0%, the lower limit of the Bi content is preferably 5.6% or more, and more preferably 6.0% or more. When the Sb content is 2.0 to 5.3%, the lower limit of the Sb content is preferably 3.0% or more. When the Sb content is 2.0 to 5.3%, the upper limit of the Sb content is preferably 5.0% or less, and more preferably 4.0% or less.
[0048] (4) Ni: 0.01-0.2% The solder alloy of the present invention suppresses the occurrence and propagation of cracks in the solder, and also suppresses the occurrence of cracks at the solder joint interface. For example, when a Cu land is soldered, an intermetallic compound of Cu6Sn5 is generated at the joint interface with the Cu land. The solder alloy of the present invention contains 0.01 to 0.2% Ni, and Ni migrates to the solder interface during soldering to form (CuNi)6Sn5 instead of Cu6Sn5, increasing the Ni concentration in the intermetallic compound layer. As a result, an intermetallic compound layer of (CuNi)6Sn5, which is finer than Cu6Sn5 and has a uniform grain size, is formed at the solder interface.
[0049] The fine (CuNi)6Sn5 intermetallic compound layer has the effect of suppressing cracks propagating from the interface. In an intermetallic compound layer with a large grain size such as Cu6Sn5, cracks propagate along the large grain size, so the cracks progress quickly. However, when the grain size is fine, the stress of the cracks is dispersed in many grain size directions, so the progression of the cracks can be slowed down.
[0050] In this way, the solder alloy according to the present invention contains Ni, which acts to make the intermetallic compound layer formed near the solder interface finer and suppress the propagation of cracks, so that the solder alloy according to the present invention can also suppress the generation of cracks from the interface.
[0051] If the Ni content is less than 0.01%, the amount of Ni at the soldering interface is small, so there is no crack suppression effect. The lower limit of the Ni content is 0.01% or more, preferably 0.03% or more. On the other hand, if the Ni content exceeds 0.2%, the liquidus temperature rises, so that the remelting of Sb added in the present invention does not occur, hindering the effect of refining SnSb. The upper limit of the Ni content is 0.2% or less, preferably 0.1% or less, and more preferably 0.05% or less.
[0052] (5) As: 0.0040-0.025% When the solder alloy according to the present invention is added to a solder paste as a solder powder, As can suppress the thickening of the solder paste. The lower limit of the As content must be 0.0040% or more in order to fully exert the effect of containing As. On the other hand, if As exceeds 0.025%, the wettability may be deteriorated. The upper limit of the As content is 0.025% or less, preferably 0.020% or less, and more preferably 0.010% or less.
[0053] In the present invention, the As-enriched layer formed by containing As refers to a region in which the As concentration is higher than the average As concentration in the solder material (the ratio of the mass of As to the mass of the solder alloy), specifically, the region from the outermost surface of the solder alloy to a depth of 2×D1 (nm) in terms of SiO2, and its presence can be confirmed by the criteria described below. The As-enriched layer is preferably present on at least a part of the surface side of the solder alloy, and preferably covers the entire surface.
[0054] The reason why the formation of an As-enriched layer by containing As as in the present invention can suppress the change in viscosity of the solder paste over time is not clear, but is presumed to be as follows. The increase in viscosity is thought to be caused by the formation of salts or the aggregation of solder powder due to reactions between Sn or Sn oxides and various additives such as activators contained in the solder paste (flux). When an As-enriched layer exists on the surface as in the solder alloy of the present invention, the As-enriched layer is interposed between the solder powder and the flux, making it difficult for the above-mentioned reactions to occur, and it is presumed that the above-mentioned effect is manifested.
[0055] (5-1) Criteria for determining As-enriched layers An arbitrary 700μm×300μm area is selected from a sample measuring 5.0mm×5.0mm (if the solder material is not in plate form, the solder material (solder powder, solder balls, etc.) is spread tightly over an area of 5.0mm×5.0mm), and an XPS analysis is performed in conjunction with ion sputtering. One area is selected for each sample, and the analysis is performed three times in total, once for each of the three samples. If S1≧S2 in all three analyses, it is determined that an As-enriched layer has been formed.
[0056] Here, the definitions of S1, S2 and D1 are as follows. S1: The integral value of the As detection intensity in the region of 0 to 2×D1 (nm) converted into SiO2 depth in the XPS analysis chart of the above sample. S2: The integral value of the As detection intensity in the region of SiO2 equivalent depth 2×D1 to 4×D1 (nm) in the XPS analysis chart D1: In the XPS analysis chart, the first SiO2 equivalent depth (nm) at which the detection intensity of O atoms becomes half the maximum detection intensity (intensity at Do·max) in a portion deeper than the SiO2 equivalent depth (Do·max (nm)) at which the detection intensity of O atoms becomes maximum.
[0057] Detailed conditions for the criteria for the above-mentioned As-enriched layer are described in the Examples. When the solder alloy according to the present invention has an As-enriched layer on the surface, it is possible to suppress an increase in the viscosity of the solder paste.
[0058] (5-2) Thickness of As-enriched Layer The thickness of the As-enriched layer (SiO2 equivalent) is 0.5 to 8.0 nm, more preferably 0.5 to 4.0 nm, and most preferably 0.5 to 2.0 nm. If the thickness of the As-enriched layer is within the above range, a solder material with excellent wettability can be obtained.
[0059] (6)In: 0.2% or less Furthermore, by containing In as an optional element, the solder alloy according to the present invention becomes a SnIn solid-solution strengthened alloy, and the temperature cycle characteristics can be improved.
[0060] The lower limit of the In content is not particularly limited, but is preferably 0.01% or more. In this range, a solid-solution strengthened alloy of SnIn is formed. The lower limit of the In content is more preferably 0.05% or more. Furthermore, if the In content is 0.2% or less, coarse SbIn compounds are not formed, and cracks occurring from inside the solder alloy can be suppressed. The upper limit of the In content is preferably 0.1% or less.
[0061] (7)Co: 0.1% or less Furthermore, the solder alloy according to the present invention can enhance the effect of Ni according to the present invention by containing Co as an optional element.
[0062] The lower limit of the Co content is not particularly limited, but is preferably 0.001% or more. Within this range, Co precipitates at the bonding interface, and exerts the effect of preventing the growth of interfacial cracks. On the other hand, if the content is preferably 0.1% or less, the intermetallic compound layer precipitated at the interface does not become thick, and the growth of cracks due to vibration, etc. can be suppressed.
[0063] When the solder alloy according to the present invention contains Co, the lower limit of the Co content is preferably 0.002% or more, further preferably 0.004% or more, particularly preferably 0.005% or more, and most preferably 0.008% or more. The upper limit of the Co content is preferably 0.05% or less, more preferably 0.012% or less, and particularly preferably 0.010% or less.
[0064] (8) Remainder: Sn The balance of the solder alloy according to the present invention is Sn. In addition to the above elements, the solder alloy may contain unavoidable impurities. Even if the solder alloy contains unavoidable impurities, the above effects are not affected.
[0065] 2. Solder paste The solder paste according to the present invention contains a flux and a solder powder. (1) Flux components The flux used in solder paste is composed of any one of the following, or a combination of two or more of: organic acids, amines, amine hydrohalides, organic halogen compounds, thixotropic agents, rosin, solvents, surfactants, base agents, polymer compounds, silane coupling agents, and colorants.
[0066] Examples of organic acids include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dimer acid, propionic acid, 2,2-bishydroxymethylpropionic acid, tartaric acid, malic acid, glycolic acid, diglycolic acid, thioglycolic acid, dithioglycolic acid, stearic acid, 12-hydroxystearic acid, palmitic acid, and oleic acid.
[0067] Amines include ethylamine, triethylamine, ethylenediamine, triethylenetetramine, 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-Cyanoethyl-2-methylimidazole, 1-Cyanoethyl-2-undecylimidazole, 1-Cyanoethyl-2-ethyl-4-methylimidazole, 1-Cyanoethyl-2-phenylimidazole, 1-Cyanoethyl-2-undecylimidazolium trimellitate, 1-Cyanoethyl-2-phenylimidazolium trimellitate, 2,4-Diamino-6-[2′-methylimidazolyl-(1′)]-ethyl-s- Triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihi hydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, 2,4-diamino-6-vinyl-s-triazine, 2,4-diamino-6-vinyl-s-triazine isocyanuric acid adduct, 2,4-Diamino-6-methacryloyloxyethyl-s-triazine, epoxy-imidazole adduct, 2-methylbenzimidazole, 2-octylbenzimidazole, 2-pentylbenzimidazole, 2-(1-ethylpentyl)benzimidazole, 2-nonylbenzimidazole, 2-(4-thiazolyl)benzimidazole, benzimidazole, 2-(2′-hydroxy-5′-methylphenyl)benzotriazole, 2-(2′-hydroxy-3′-tert-butyl-5′-methylphenyl)-5-chlorobenzotriazole, 2-(2′-hydroxy-3′,5′-di-tert-amylphenyl)benzotriazole, 2-(2′-hydroxy-5′-tert-octylphenyl)benzotriazole, 2,2′-methylenebis[6-(2H-benzotriazol-2-yl)-4-tert-octylphenol], 6 -(2-benzotriazolyl)-4-tert-octyl-6'-tert-butyl-4'-methyl-2,2'-methylenebisphenol, 1,2,3-benzotriazole, 1-[N,N-bis(2-ethylhexyl)aminomethyl]benzotriazole, carboxybenzotriazole, 1-[N,N-bis(2-ethylhexyl)aminomethyl]methylbenzotriazole, 2,2'-[[(methyl-1H-benzotriazol-1-yl)methyl]imino]bisethanol, 1-(1',2'-dicarboxyethyl)benzotriazole, 1-(2,3-dicarboxypropyl)benzotriazole, 1-[(2-ethylhexylamino)methyl]benzotriazole, 2,6-bis[(1H-benzotriazol-1-yl)methyl]-4-methylphenol, 5-methylbenzotriazole, 5-phenyltetrazole, etc.,
[0068] Amine hydrohalides are compounds obtained by reacting an amine with a hydrogen halide. Examples of the amine include ethylamine, ethylenediamine, triethylamine, diphenylguanidine, ditolylguanidine, methylimidazole, and 2-ethyl-4-methylimidazole. Examples of the hydrogen halide include chlorine, bromine, and iodine hydrides.
[0069] Examples of the organic halogen compound include trans-2,3-dibromo-2-butene-1,4-diol, triallyl isocyanurate hexabromide, 1-bromo-2-butanol, 1-bromo-2-propanol, 3-bromo-1-propanol, 3-bromo-1,2-propanediol, 1,4-dibromo-2-butanol, 1,3-dibromo-2-propanol, 2,3-dibromo-1-propanol, 2,3-dibromo-1,4-butanediol, and 2,3-dibromo-2-butene-1,4-diol.
[0070] Examples of the thixotropic agent include wax-based thixotropic agents, amide-based thixotropic agents, and sorbitol-based thixotropic agents. Examples of the wax-based thixotropic agents include castor hardened oil. Examples of the amide-based thixotropic agents include monoamide-based thixotropic agents, bisamide-based thixotropic agents, and polyamide-based thixotropic agents, and more specifically, lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, hydroxystearic acid amide, saturated fatty acid amide, oleic acid amide, erucic acid amide, unsaturated fatty acid amide, p-toluenemethane amide, aromatic amide, and methylenebisstearic acid amide. Examples of the sorbitol-based thixotropic agents include dibenzylidene-D-sorbitol, bis(4-methylbenzylidene)-D-sorbitol, etc. Examples of the sorbitol-based thixotropic agents include dibenzylidene-D-sorbitol, bis(4-methylbenzylidene)-D-sorbitol, etc. Examples of the sorbitol-based thixotropic agents include dibenzylidene-D-sorbitol, bis(4-methylbenzylidene)-D-sorbitol, etc.
[0071] Examples of the base agent include nonionic surfactants, weak cationic surfactants, and rosin.
[0072] Examples of the nonionic surfactant include polyethylene glycol, polyethylene glycol-polypropylene glycol copolymers, aliphatic alcohol polyoxyethylene adducts, aromatic alcohol polyoxyethylene adducts, and polyhydric alcohol polyoxyethylene adducts.
[0073] Examples of the weak cationic surfactant include diamine-terminated polyethylene glycol, diamine-terminated polyethylene glycol-polypropylene glycol copolymer, aliphatic amine polyoxyethylene adducts, aromatic amine polyoxyethylene adducts, and polyvalent amine polyoxyethylene adducts.
[0074] Examples of rosin include raw rosins such as gum rosin, wood rosin, and tall oil rosin, as well as derivatives obtained from the raw rosins. Examples of the derivatives include refined rosin, hydrogenated rosin, disproportionated rosin, polymerized rosin, and α,β-unsaturated carboxylic acid modified products (acrylated rosin, maleic rosin, fumarated rosin, etc.), as well as purified products, hydrogenated products, and disproportionated products of the polymerized rosin, as well as purified products, hydrogenated products, and disproportionated products of the α,β-unsaturated carboxylic acid modified products, and two or more of them can be used. In addition to the rosin-based resin, the composition can further contain at least one resin selected from terpene resins, modified terpene resins, terpene phenolic resins, modified terpene phenolic resins, styrene resins, modified styrene resins, xylene resins, and modified xylene resins. Examples of the modified terpene resins that can be used include aromatic modified terpene resins, hydrogenated terpene resins, and hydrogenated aromatic modified terpene resins. Examples of the modified terpene phenolic resins that can be used include hydrogenated terpene phenolic resins. The modified styrene resin may be a styrene-acrylic resin, a styrene-maleic acid resin, etc. The modified xylene resin may be a phenol-modified xylene resin, an alkylphenol-modified xylene resin, a phenol-modified resol-type xylene resin, a polyol-modified xylene resin, a polyoxyethylene-added xylene resin, etc.
[0075] Examples of the solvent include water, alcohol-based solvents, glycol ether-based solvents, terpineols, etc. Examples of the alcohol-based solvent include isopropyl alcohol, 1,2-butanediol, isobornylcyclohexanol, 2,4-diethyl-1,5-pentanediol, 2,2-dimethyl-1,3-propanediol, 2,5-dimethyl-2,5-hexanediol, 2,5-dimethyl-3-hexyne-2,5-diol, 2,3-dimethyl-2,3-butanediol, 1,1,1-tris(hydroxymethyl)ethane, 2-ethyl-2-hydroxymethyl-1,3-propanediol, 2,2′-oxybis(methylene)bis(2-ethyl -1,3-propanediol), 2,2-bis(hydroxymethyl)-1,3-propanediol, 1,2,6-trihydroxyhexane, bis[2,2,2-tris(hydroxymethyl)ethyl]ether, 1-ethynyl-1-cyclohexanol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, erythritol, threitol, guaiacol glycerol ether, 3,6-dimethyl-4-octyne-3,6-diol, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, etc. Examples of glycol ether solvents include diethylene glycol mono-2-ethylhexyl ether, ethylene glycol monophenyl ether, 2-methylpentane-2,4-diol, diethylene glycol monohexyl ether, diethylene glycol dibutyl ether, triethylene glycol monobutyl ether, etc.
[0076] Examples of the surfactant include polyoxyalkylene acetylene glycols, polyoxyalkylene glyceryl ethers, polyoxyalkylene alkyl ethers, polyoxyalkylene esters, polyoxyalkylene alkylamines, and polyoxyalkylene alkylamides.
[0077] (2) Flux content The content of the flux is preferably 5 to 95% and more preferably 5 to 15% based on the total mass of the solder paste, in which case the effect of suppressing thickening caused by the solder powder is sufficiently exhibited.
[0078] (3) Solder powder The solder powder used in the solder paste according to the present invention is preferably a spherical powder, which improves the fluidity of the solder alloy.
[0079] Furthermore, when the solder alloy is a spherical powder, if it has a size (particle size distribution) corresponding to symbols 1 to 8 in the powder size classification (Table 2) in JIS Z 3284-1:2014, soldering to fine components becomes possible. The size of the particulate solder material is more preferably a size corresponding to symbols 4 to 8, and even more preferably a size corresponding to symbols 5 to 8. The sphericity is preferably 0.90 or more, more preferably 0.95 or more, and most preferably 0.99 or more.
[0080] In the present invention, the diameter and sphericity of the solder alloy, which is a spherical powder, are measured using a CNC image measuring system (Ultra Quick Vision ULTRA QV350-PRO measuring device manufactured by Mitutoyo Corporation) that uses the minimum zone center method (MZC method). In the embodiment, the sphericity indicates the deviation from a true sphere, and is, for example, the arithmetic mean value calculated when the diameter of each of 500 balls is divided by the major axis, and the closer the value is to the upper limit of 1.00, the closer the ball is to a true sphere.
[0081] (4) Manufacturing method of solder paste The solder paste according to the present invention is manufactured by a method generally used in the industry. First, the solder powder can be manufactured by a known method such as a dripping method in which molten solder material is dripped to obtain particles, a spraying method in which centrifugal spraying is performed, or a method in which bulk solder material is crushed. In the dripping method or spraying method, the dripping or spraying is preferably performed in an inert atmosphere or a solvent in order to obtain particles. Then, the above components are heated and mixed to prepare a flux, and the above solder powder is introduced into the flux, stirred, and mixed to manufacture the solder paste.
[0082] 3. Solder balls The solder alloy according to the present invention can be used as a solder ball. When used as a solder ball, the solder alloy according to the present invention can be manufactured into a solder ball by a dropping method, which is a common method in the industry. Also, a solder joint can be manufactured by processing the solder ball by a common method in the industry, such as mounting one solder ball on one electrode coated with flux and joining them. The particle size of the solder ball is preferably 1 μm or more, more preferably 10 μm or more, even more preferably 20 μm or more, and particularly preferably 30 μm or more. The upper limit of the particle size of the solder ball is preferably 3000 μm or less, more preferably 1000 μm or less, even more preferably 600 μm or less, and particularly preferably 600 μm or less.
[0083] 4. Solder preform The solder alloy according to the present invention can be used as a preform, which may be in the form of a washer, ring, pellet, disk, ribbon, wire, or the like.
[0084] 5. Solder joints The solder alloy according to the present invention can be used to form a solder joint by joining an electrode of a PKG (Package) such as an IC chip to an electrode of a substrate such as a PCB (Printed Circuit Board). The solder joint according to the present invention is composed of an electrode and a solder joint. The solder joint refers to a portion that is mainly formed of the solder alloy.
[0085] 6.In-vehicle electronic circuit, ECU electronic circuit, in-vehicle electronic circuit device, ECU electronic circuit device As is clear from the above description, the solder alloy according to the present invention has excellent heat cycle properties, and the occurrence and propagation of cracks in the solder alloy is suppressed. Therefore, even if the solder alloy is used in an automobile, which is used under conditions of constant vibration, that is, as an in-vehicle component, the growth and development of cracks is not promoted. Therefore, since the solder alloy according to the present invention has such particularly remarkable properties, it is understood that the solder alloy according to the present invention is particularly suitable for soldering electronic circuits mounted on automobiles.
[0086] As used herein, "excellent heat cycle resistance" refers to a condition in which, even when a heat cycle test is conducted from -40°C to +125°C, as shown in the examples described later, the crack occurrence rate after 3,000 cycles is 90% or less, and similarly, the remaining shear strength rate after 3,000 cycles is 30% or more.
[0087] These characteristics mean that even if used under extremely harsh conditions such as the above-mentioned heat cycle test, the in-vehicle electronic circuit will not break, i.e., will not become unusable or malfunction. The solder alloy according to the present invention is highly reliable, particularly as a solder alloy used for soldering ECUs. Furthermore, the solder alloy according to the present invention has an excellent shear strength retention rate after temperature cycles. In other words, even if used for a long period of time, resistance to external forces such as shear strength against external forces applied from the outside, such as collisions and vibrations, does not decrease.
[0088] Thus, the solder alloy according to the present invention is used, more particularly, for soldering in-vehicle electronic circuits or for soldering ECU electronic circuits, and exhibits excellent heat cycle properties.
[0089] An "electronic circuit" is a system that performs a desired function as a whole through the electronic engineering combination of multiple electronic components, each of which has its own function.
[0090] Examples of electronic components that make up such electronic circuits include chip resistor components, multiple resistor components, QFP, QFN, power transistors, diodes, capacitors, etc. Electronic circuits incorporating these electronic components are mounted on a substrate to form an electronic circuit device.
[0091] In the present invention, the substrate constituting such an electronic circuit device, for example, a printed wiring board, is not particularly limited. The material is also not particularly limited, but a heat-resistant plastic substrate (e.g., FR-4 with high Tg and low CTE) is an example. The printed wiring board is preferably a printed circuit board in which the surface of the Cu land is treated with an organic substance (OSP: Organic Surface Protection) such as amine or imidazole.
[0092] 7. Method of forming solder alloy There is no limitation on the method for producing the solder alloy according to the present invention, and the solder alloy can be produced by melting and mixing raw material metals.
[0093] There is no limitation on the method of forming an As-enriched layer in a solder alloy. One example of the method of forming an As-enriched layer is to heat a solder material in an oxidizing atmosphere (air or oxygen atmosphere). The heating temperature is not limited, but may be, for example, 40 to 200°C, or may be 50 to 80°C. The heating time is also not limited, and may be, for example, several minutes to several days, preferably several minutes to several hours. In order to form a sufficient amount of an As-enriched layer, the heating time is preferably 10 minutes or more, more preferably 20 minutes or more. The above-mentioned solder powder, solder ball, and solder preform can also be subjected to this heat treatment to form an As-enriched layer.
[0094] The solder alloy according to the present invention can be manufactured by using a low alpha ray material as its raw material. When such a low alpha ray alloy is used to form solder bumps around a memory, it becomes possible to suppress soft errors. EXAMPLES
[0095] Using the solder alloys (mass %) shown in the examples and comparative examples in Tables 1 to 4, 1. temperature cycle test (crack reliability and shear strength reliability), 2. As surface concentration, and 3. inhibition of thickening were evaluated.
[0096] 1. Temperature cycle test (1-1) Crack reliability (crack rate) The solder alloys in Tables 1 to 4 were atomized to prepare solder powder. The solder alloys were mixed with soldering flux consisting of rosin, solvent, activator, thixotropic agent, organic acid, etc. to prepare solder pastes of each solder alloy. The solder pastes were printed on a 6-layer printed circuit board with a 150 μm metal mask, and then 3216 chip resistors were mounted with a mounter. Test boards were prepared by reflow soldering at a maximum temperature of 235° C. in the examples and at a maximum temperature of 280° C. in the comparative examples, with a holding time of 40 seconds. The solder powders used had an average particle size of 21 μm and were classified as 5 in the powder size classification (Table 2) of JIS Z3284-1:2014. The solder powders were obtained by heating at 60° C. for 30 minutes in the atmosphere using a drying device. Only in Comparative Example 25 was solder powder that was not subjected to heat treatment used.
[0097] Test boards soldered with each solder alloy were placed in a temperature cycle tester set to low temperature of -40°C, high temperature of +125°C, and a holding time of 30 minutes. After 3,000 cycles, they were removed from the temperature cycle tester under each condition, and the condition of cracks was observed using a 150x metallurgical microscope. The crack rate was measured based on the estimated total crack length.
[0098] Crack rate (%) = (total crack length) x 100 / (total expected line crack length) Here, "anticipated total length of linear crack" refers to the crack length of complete fracture. The crack rate is the ratio obtained by dividing the total length of the multiple cracks 6 shown in Fig. 1 by the length of the predicted crack propagation path 8. In this embodiment, when the crack rate is 90% or less, the crack reliability is marked as "○" since it is not a problem in practical use, and when it exceeds 90%, the crack reliability is marked as "×".
[0099] (1-2) Shear strength reliability (shear strength survival rate) The shear strength reliability is an index of the degree to which the shear strength of a solder joint is maintained during a temperature cycle test, compared to the shear strength of the solder joint in its initial state before the temperature cycle test.
[0100] The shear strength test was performed using a joint strength tester STR-000 at room temperature, at a test speed of 6 mm / min, and at a test height of 50 μm. The shear strength residual rate (%) was calculated by (initial shear strength)×100 / (shear strength after temperature cycle test). In this embodiment, when the shear strength residual rate was 30% or more, the shear strength reliability was evaluated as "○" since it was practically acceptable, and when it was less than 30%, the shear strength reliability was evaluated as "×".
[0101] 2.As surface concentration The surface concentration of As was evaluated by depth direction analysis using XPS (X-ray Photoelectron Spectroscopy) as follows.
[0102] (Analysis conditions) Analytical equipment: Micro-area X-ray photoelectron spectrometer (AXIS Nova manufactured by Kratos Analytical) Analysis conditions: X-ray source AlKα ray, X-ray gun voltage 15 kV, X-ray gun current value 10 mA, analysis area 700 μm × 300 μm Sputtering conditions: Ion type: Ar+, Acceleration voltage: 2kV, Sputtering rate: 0.5nm / min (SiO2 equivalent) Samples: The solder powder obtained in "1. Temperature cycle test" was spread evenly without any gaps on a stage with carbon tape attached, and three samples were prepared. The size of the samples was 5.0 mm x 5.0 mm. The solder powder used had an average particle size of 21 μm, which corresponds to powder size classification 5 of JIS Z3284-1:2014 (Table 2).
[0103] (Evaluation Procedure) An area of 700μm×300μm was selected from a sample measuring 5.0mm×5.0mm, and XPS analysis was performed on each of the Sn, O, and As atoms while performing ion sputtering to obtain an XPS analysis chart. One area was selected for each sample, and the analysis was performed once for each of the three samples, for a total of three times.
[0104] Examples of charts obtained by XPS analysis are shown in Figures 2 to 4. Figures 2 to 4 show the same sample with the scale of detection intensity (cps) on the vertical axis changed, and the horizontal axis is the SiO2 equivalent depth (nm) calculated from the sputtering time. In the XPS analysis chart, the vertical axis is detection intensity (cps) and the horizontal axis can be selected from either the sputtering time (min) or the SiO2 equivalent depth (nm) calculated from the sputtering time using the sputtering etching rate of a SiO2 standard sample, but in Figures 2 to 4, the horizontal axis in the XPS analysis chart is the SiO2 equivalent depth (nm) calculated from the sputtering time using the sputtering etching rate of a SiO2 standard sample.
[0105] In the XPS analysis chart of each sample, the SiO2 equivalent depth at which the detection intensity of O atoms was maximum was defined as Do·max (nm) (see Figure 3). The first SiO2 equivalent depth deeper than Do·max at which the detection intensity of O atoms was half the maximum detection intensity (intensity at Do·max) was defined as D1 (nm).
[0106] Next, in the XPS analysis chart of each sample, the integral value (S1) of the As detection intensity in the region from the outermost surface to a depth of 2×D1 (the region with a SiO2-equivalent depth of 0 to 2×D1 (nm)) and the integral value (S2) of the As detection intensity in the region from the depth of 2×D1 to a further depth of 2×D1 (the region with a SiO2-equivalent depth of 2×D1 to 4×D1 (nm)) (see Figure 4) were calculated and compared.
[0107] And the evaluation was carried out based on the following criteria. -S1>S2 in all three measurements : As-enriched layer is formed (○) -S1>S2 in 2 or less of the 3 measurements : No As-enriched layer is formed (×) 3. Suppression of thickening The solder powder obtained in "1. Temperature cycle test" and the flux shown in Table 5 were heated and stirred so that the mass ratio of the flux to the solder powder (flux:solder powder) was 11:89, and then cooled to prepare solder pastes. The viscosity of these solder pastes was measured for 12 hours using a rotational viscometer (PCU-205, manufactured by Malcom Co., Ltd.) at a rotation speed of 10 rpm and a measurement temperature of 25°C according to the method described in "4.2 Viscosity characteristic test" of JIS Z 3284-3:2014. The initial viscosity (viscosity after 30 minutes of stirring) was compared with the viscosity after 12 hours, and the viscosity increase suppression effect was evaluated based on the following criteria. Viscosity after 12 hours ≦ Initial viscosity × 1.2: Viscosity increase over time is small and good (○) Viscosity after 12 hours > initial viscosity x 1.2: Viscosity increase over time is large, poor (×)
[0108] [Table 1]
[0109] [Table 2]
[0110] [Table 3]
[0111] [Table 4]
[0112] [Table 5]
[0113] As shown in Tables 1 to 4, it was found that Examples 1 to 128, regardless of the alloy composition, meet all the requirements of the present invention, have excellent crack reliability and shear strength reliability, have As surface enrichment, and also have a thickening suppression effect. In addition, it was found that all of them have an As enriched layer, and the change in viscosity of the solder paste over time is suppressed, and the yellowing when the solder piece is heated is also suppressed. On the other hand, it was found that Comparative Examples 1 to 24 do not meet at least one of the requirements of the present invention regardless of the alloy composition, and at least one of the above effects is inferior. Comparative Example 23 had a large amount of As and was poor in wettability, so a solder joint could not be formed, and therefore crack reliability and shear strength reliability could not be evaluated. Comparative Example 25 did not undergo heat treatment, so no As enriched layer was formed, and no thickening suppression effect was obtained. [Explanation of symbols]
[0114] 1 Chip components 2. Solder Alloys 3. Substrate 4 Cu Land 5 Intermetallic compound layer 6 Crack propagation path 8. Expected crack propagation path
Claims
1. The solder alloy has an As-enriched layer, and the presence of the As-enriched layer is confirmed by the following criteria: the As-enriched layer is formed by dividing the As-enriched layer by the thickness of the solder alloy from the outermost surface to the SiO 2 The As-enriched layer is a region up to a depth of 2×D1 (nm) in terms of the converted depth. 2 A solder alloy having a converted thickness of 0.5 to 8.0 nm. (Judgment criteria) An arbitrary area of 700 μm×300 μm is selected from a sample measuring 5.0 mm×5.0 mm, and an XPS analysis is performed in combination with ion sputtering. One area is selected for each sample, and three analyses are performed once for each of the three samples, for a total of three analyses. If S1>S2 in all three analyses, it is determined that an As-enriched layer has been formed. Where: S1: In the XPS analysis chart, SiO 2 The integral value of the As detection intensity in the region of 0 to 2×D1 (nm) converted depth S2: In the XPS analysis chart, SiO 2 The integral value of the As detection intensity in the region of 2×D1 to 4×D1 (nm) converted depth D1: SiO where the detection intensity of O atoms was maximum in the XPS analysis chart 2 The first SiO where the detection intensity of O atoms is 1 / 2 of the maximum detection intensity (intensity at Do max) in a portion deeper than the conversion depth (Do max (nm)). 2 The equivalent depth (nm).
2. The lead-free solder alloy according to claim 1 , further comprising, by mass%, In: 0.2% or less.
3. The solder alloy according to claim 1 or 2, further comprising, by mass%, Co: 0.1% or less.
4. A solder paste comprising a solder powder made of the solder alloy according to any one of claims 1 to 3 and a flux.
5. A solder ball made of the solder alloy according to any one of claims 1 to 3.
6. A solder preform comprising the solder alloy according to any one of claims 1 to 3.
7. A solder joint formed from the solder alloy according to any one of claims 1 to 3.
8. An on-vehicle electronic circuit comprising the solder alloy according to any one of claims 1 to 3.
9. An ECU electronic circuit comprising the solder alloy according to any one of claims 1 to 3.
10. An on-vehicle electronic circuit device comprising the on-vehicle electronic circuit according to claim 8.
11. An ECU electronic circuit device comprising the ECU electronic circuit according to claim 9.
Citation Information
Patent Citations
Solder alloys, solder pastes, solder balls, solder preforms, solder joints, on-board electronic circuits, ECU electronic circuits, on-board electronic circuit devices, and ECU electronic circuit devices
JP6810375B1
Solder alloy, solder paste, and electronic circuit board
WO2014003006A1
Lead-free solder alloy and in-vehicle electronic circuit
WO2014163167A1
Lead-free solder alloy, flux composition, solder paste composition, electronic circuit board and electronic control device
WO2017164194A1
Solder material, solder paste, and solder joint
WO2019103025A1